CT and MR Imaging of Neuroaxonal Leukodystrophy Presenting as Early-Onset Frontal Dementia - Mascalchi, M.; Gavazzi, C.; Morbin, M.; Giaccone, G.; Arnetoli, G.; Zappoli, R.; Bugiani, O. (American Journal of Neuroradiology, 2006)
SUMMARY: CT and MR imaging showed diffuse changes of the frontal white matter and genu of the corpus callosum with minimal atrophy and no contrast enhancement in a 41-year-old woman with progressive dementia. Brain biopsy disclosed axonal spheroids and gliosis in the white matter without macrophage or inflammatory infiltration or vessel abnormalities consistent with neuroaxonal leukodystrophy. This disease can be suspected on CT and MR imaging findings but requires neuropathologic examination to be diagnosed.